Epidemiology of osteoarthritis and associated comorbidities in the United Kingdom - Swain, Subhashisa (2021)
Background Osteoarthritis (OA) is very common and is the main cause of chronic joint pain and disability in older people. According to this systematic review nearly 67% of people with OA had comorbidity. There is little information available on how the incidence and prevalence of OA has changed over the past 20 years in the UK, and what is the likelihood of having other chronic conditions, their progression, and associated outcomes.